Therapeutic enteroscopy using a new single-balloon enteroscope: a case series - Moreels, Tom G.; Kouinche Madenko, Nathalie; Taha, Alaa; Piessevaux, Hubert; Deprez, Pierre H. (Endoscopy International Open, 2016)
Background and study aims: Balloon-assisted enteroscopy allows therapeutic intervention in the small bowel, and even of the biliopancreatic system in patients with altered anatomy. However, the conventional single-balloon enteroscope (SBE) has limited therapeutic use because of its small-caliber working channel and the lack of an additional water jet channel. The new single-balloon enteroscope prototype XSIF-180JY has been developed to overcome these problems. We present experience with use of the new SBE prototype during 14 therapeutic endoscopy procedures, which illustrates its advantages. Patients and methods: During a 2-month period, 16 SBE procedures were performed (2 antegrade, 2 retrograde and 12 ERCP procedures) using the XSIF-180JY prototype, 14 of which were done with therapeutic intent. Results: The XSIF-180JY SBE allowed deep enteroscopy with balloon dilation and multiple intestinal polypectomies. Moreover, 14 ERCP procedures were successfully performed in 12 patients with Roux-en-Y altered anatomy. Sphincterotomy, balloon dilation, stone extraction and 7 Fr plastic stent placement were performed through the 3.2-mm working channel. The additional water jet was useful for flushing away stone fragments from the intrahepatic bile ducts and the retrieval basket and for flushing away blood from a bleeding sphincterotomy. No complications related to the enteroscope were encountered.Conclusions: The new therapeutic XSIF-180JY SBE permitted therapeutic enteroscopy and ERCP through its 3.2-mm working channel and the additional water jet channel proved useful in flushing away biliary stones and blood without the need to clear the working channel. This newly developed SBE has the advantage of a larger working channel and an additional water jet, improving therapeutic enteroscopy.